Case study - plans and strategies for the 700Mhz band in the Caribbean - Leith, Christa Onika (2015)
Examines the allocation of spectrum on the 700Mhz band across the Caribbean and posits that allocation methodologies and roll out conditions and obligations should be designed and attached to all awards of spectrum so as to faciliate increased competition and achievement of stated objectives.